Studies on clinical signs, vaginoscopy and vaginal cytology for predicting appropriate breeding time in bitches - ARUNMOZHI, N; NAIDU, K VENUGOPAL; SREENU, MAKKENA; RAO, A S (The Indian Journal of Animal Reproduction, 2023)
A comparative study for the reliability on clinical signs, vaginoscopy and vaginal cytology for detecting appropriatebreeding time in bitches was carried out. The clinical signs of estrus was characterized by decrease in vulvul oedema and softappearance of vulva is 91.67% of the cases. The vaginoscopy at the estrus revealed dense creamy or paper while mucosa andangulated mucosa! shrinkage in all the bitches studied. Vaginal cytology revealed more than 95% superficial cells, an indicator ofoestrus in 91.67% of bitches. Thus vaginal endoscopy was found to be more specific for estrus detection and for better breedingmanagement followed by vaginal cytology and clinical symptoms.
Keywords: Clinical signs; vaginoscopy; vaginal cytology; bitches